(untitled) (Signifiances (Signifying), 2017)
This paper presents an account of the phenomenon of mental construal manifested in English expressions of stance through the distinction of clauses that are headed by subjects associated with two conceptual archetypes: participant (P) invoked by the first-person pronoun (‘I am certain that’) and abstract setting (S) conveyed by anticipatory ‘it’ (‘It is certain that’). With recourse to the main theoretical points on the anchoring of linguistic meaning in the acts of mental construal and interactive coordination, the conducted analysis focuses on a corpus of about 350 examples that represent narrative and dialogic discourse in English-language fiction. It shown that the choice of stance expressions with P- and S-subjects is motivated by the distinctions that arise in discourse between actual and mentally represented types of reality, the contrast between reference-making and viewing as types of cognitive operations and the associated narrative and dialogic strategies.